#TITLE_ALTERNATIVE# - PUTERA (NIM : 10206013); Pembimbing Tugas Akhir Gunawan Handayani, MSCE, Ph.D, ALESSANDRO
Refraction Microtremor (ReMi) is one of the methods that used in geotechnical engineering to determine the S wave velocity profile. The S wave velocity profile was obtained from the Rayleigh wave which has the largest amplitude waves than the other. Ambient Noise was used to generate the Rayleigh wave that in former methods treated as a nuisance that should be eliminated. The acquisition of ReMi data using ordinary refraction configuration that commonly used to find the P wave profile.